Gelsolin Attenuates Neonatal Hyperoxia-Induced Inflammatory Responses to Rhinovirus Infection and Preserves Alveolarization - Cui, Tracy X.; Brady, Alexander E.; Zhang, Ying-Jian; Fulton, Christina T.; Popova, Antonia P. (Frontiers in Immunology, 2022)
Prematurity and bronchopulmonary dysplasia (BPD) increase the risk of asthma later in life. Supplemental oxygen therapy is a risk factor for chronic respiratory symptoms in infants with BPD. Hyperoxia induces cell injury and release of damage-associated molecular patterns (DAMPs). Cytoskeletal filamentous actin (F-actin) is a DAMP which binds Clec9a, a C-type lectin selectively expressed on CD103+ dendritic cells (DCs). Co-stimulation of Clec9a and TLR3 induces maximal proinflammatory responses. We have shown that neonatal hyperoxia (a model of BPD) increases lung IL-12+Clec9a+CD103+ DCs, pro-inflammatory responses and airway hyperreactivity following rhinovirus (RV) infection. CD103+ DCs and Clec9a are required for these responses. Hyperoxia increases F-actin levels in bronchoalveolar lavage fluid (BALF). We hypothesized that the F-actin severing protein gelsolin attenuates neonatal hyperoxia-induced Clec9a+CD103+ DC-dependent pro-inflammatory responses to RV and preserves alveolarization. We exposed neonatal mice to hyperoxia and treated them with gelsolin intranasally. Subsequently we inoculated the mice with RV intranasally. Alternatively, we inoculated normoxic neonatal mice with BALF from hyperoxia-exposed mice (hyperoxic BALF), RV and gelsolin. We analyzed lung gene expression two days after RV infection. For in vitro studies, lung CD11c+ cells were isolated from C57BL/6J or Clec9agfp-/- mice and incubated with hyperoxic BALF and RV. Cells were analyzed by flow cytometry. In neonatal mice, gelsolin blocked hyperoxia-induced Il12p40, TNF-α and IFN-γ mRNA and protein expression in response to RV infection. Similar effects were observed when gelsolin was co-administered with hyperoxic BALF and RV. Gelsolin decreased F-actin levels in hyperoxic BALF in vitro and inhibited hyperoxia-induced D103lo DC expansion and inflammation in vivo. Gelsolin also attenuated hyperoxia-induced hypoalveolarization. Further, incubation of lung CD11c+ cells from WT and Clec9agfp-/- mice with hyperoxic BALF and RV, showed Clec9a is required for maximal hyperoxic BALF and RV induced IL-12 expression in CD103+ DCs. Finally, in tracheal aspirates from mechanically ventilated human preterm infants the F-actin to gelsolin ratio positively correlates with FiO2, and gelsolin levels decrease during the first two weeks of mechanical ventilation. Collectively, our findings demonstrate a promising role for gelsolin, administered by inhalation into the airway to treat RV-induced exacerbations of BPD and prevent chronic lung disease.